Ventilatory efficiency slope is associated with cardiopulmonary complications after thoracoscopic anatomical lung resection. (14th February 2022) - Bédat, Benoît; Koliakos, Evangelos; Demarchi, Marco S; Perentes, Jean; Licker, Marc-Joseph; Triponez, Frédéric; Krueger, Thorsten; Karenovics, Wolfram; Gonzalez, Michel
Abstract: OBJECTIVES: The aim of this study was to identify whether steeper V.E/V. CO2 slope was associated with cardiopulmonary complications (CPC) after anatomical resection by video-assisted thoracic surgery. Long-term survival was analysed as secondary outcome. METHODS: We reviewed the files of all consecutive patients who underwent pulmonary anatomical resections by video-assisted thoracic surgery between January 2010 and October 2020 at the Centre for Thoracic Surgery of Western Switzerland. Logistic regression was used to investigate the risk of CPC associated with the V.E/V.CO2 slope and other possible confounders. Survival was analysed with Kaplan–Meier curves. Risk factors associated with survival were analysed with a Cox proportional hazards model. RESULTS: The V.E/V.CO2 slope data were available for 145 patients [F/M: 66/79; mean age (standard deviation): 65.8 (8.9)], which were included in the analysis. Patients underwent anatomical resection [lobectomy (71%) or segmentectomy (29%)] mainly for lung cancer (96%). CPC and all-cause 90-day mortality were 29% and 1%, respectively. The mean (standard deviation) percentage of the predicted V . O2peak was 70% (17). Maximum effort during cardiopulmonary exercise test was reached in only 31% of patients. The V.E/V.CO2 slope (standard deviation) was not different if the maximum effort was reached or not [39 (6) vs 37 (7), P = 0.21]. V.E/V.CO2 slope >35 was associated with an increased risk of CPC (odds ratio 2.9, 95% confidence interval 1.2, 7.2, P = 0.020). V.E/V.CO2 slope >35 was not associated with shorter survival censored for lung cancer-related death. CONCLUSIONS: V . E/V . CO2 slope >35 is significantly associated with postoperative CPC after anatomical resections by video-assisted thoracic surgery. Clinical registration number CER-VD (Switzerland): Project ID: 2021-00620. Abstract : Pulmonary anatomical resection can be proposed for patients with early-stage non-small cell lung cancer, for benign lesions or for metastases.